2021
DOI: 10.3389/fnut.2021.646819
|View full text |Cite
|
Sign up to set email alerts
|

High Red Meat Intake Exacerbates Dextran Sulfate-Induced Colitis by Altering Gut Microbiota in Mice

Abstract: Inflammatory bowel disease (IBD) is a serious hazard to public health, but the precise etiology of the disease is unclear. High intake of red meat diet is closely related to the occurrence of IBD. In this study, we investigated whether the high intake of red meat can increase the sensitivity of colitis and the underlying mechanism. Mice were fed with different levels of red meat for 8 weeks and then the colonic contents were analyzed by 16S rRNA sequencing. Then 3% dextran sulfate sodium was used to induce col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 65 publications
(74 reference statements)
2
25
0
2
Order By: Relevance
“…The genus Lachnospiraceae_NK4A136_group can prevent and treat acute colitis [ 49 ]. Some researchers have found that Lachnospiraceae_NK4A136_group is butyrate-producing bacteria, and butyrate protects the intestinal mucosa and reduces host inflammation [ 50 , 51 ]. In the present study, we observed a remarkable increase in the abundance of Lachnospiraceae_NK4A136_group in the HFC group, suggesting that CPP supplementation protects the intestinal mucosa and reduces the occurrence of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The genus Lachnospiraceae_NK4A136_group can prevent and treat acute colitis [ 49 ]. Some researchers have found that Lachnospiraceae_NK4A136_group is butyrate-producing bacteria, and butyrate protects the intestinal mucosa and reduces host inflammation [ 50 , 51 ]. In the present study, we observed a remarkable increase in the abundance of Lachnospiraceae_NK4A136_group in the HFC group, suggesting that CPP supplementation protects the intestinal mucosa and reduces the occurrence of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Statole and indole are typtophan metabolites, and statole was found to be associated with the pathogenesis of IBD via inducing intestinal epithelial death [ 52 ]. Furthermore, a high intake of red meat resulted in reduced abundance of Lachnospiraceae_NK4A136_group , Faecalibaculum , Blautia and Dubosiella , and increased abundance of Bacteroides and Alistipes in dextran sulfate sodium (DSS)-induced colitis [ 38 ]. Most of the studies found the negative effect of excessive intake of animal protein, especially red meat, while soy-pea protein was considered having a protective effect [ 53 ].…”
Section: Westernized Diet Gut Dysbiosis and Ibdmentioning
confidence: 99%
“…44 Alistipes is considered as a pathogenic bacteria associated with the development of colitis. 45 The abundance of Rikenella , a genus in the Rikenellaceae family, is significantly increased in the immune system diseases. 46 In the present study, DSS treatment increased the relative abundances of the harmful microbes, which confirmed previous studies.…”
Section: Discussionmentioning
confidence: 99%